THE RELATIONSHIP BETWEEN STUDENTS’ LEVEL OF POSITIVE THINKING AND THEIR ENGLISH SPEAKING ANXIETY - Desyfani Zaenab Rahman; Nita Kaniadewi (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Every student wanted to speak in English without feeling anxious, many of them really suffered from anxiety. Students who have negative thoughts while they are speaking in English, caused the negative result. Meanwhile, students who have positive thinking while they are speaking in English, will have positive result. The present study employed a quantitative approach, wherein a questionnaire was administered to a sample of 67 second-semester students enrolled in the English Education program at the University of Muhammadiyah Prof. Dr. HAMKA. The sample was collected with the use of the purposive sampling method. The result shows that the data calculated were rvalue= 0.315, rvalue ? N.Sig 5% (0.315 ? 0.01), and it was rvalue ? rtable (0.315 ? 0.240) and tvalue ? ttable (2.673 ? 1.996). As a result, the null hypothesis (Ho) was rejected and the alternative hypothesis (Hi) was accepted. So, it told that there was a negative correlation between students’ level of positive thinking and their English speaking anxiety, and it was 0.315 in the low category.